2013
DOI: 10.1007/s00259-013-2448-1
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT in HIV-related central nervous system pathology

Abstract: ¹⁸F-FDG PET/CT is particularly useful for differentiating between infection and PCNSL in HIV-infected patients with a cerebral lesion on MRI or CT. ¹⁸F-FDG PET/CT was also a helpful tool in the diagnostic work-up of patients with other HIV-related cerebral pathology. Additional advantages of ¹⁸F-FDG PET/CT are the abilities to assess abnormally increased glucose metabolism in the body and to identify potential sites for biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…Taking several studies together, this technique has a diagnostic sensitivity in PCNSL of 76%–100% [4, 28]. Maximum standardized uptake value (SUVmax) is higher in PCNSL than in gliomas [29, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…Taking several studies together, this technique has a diagnostic sensitivity in PCNSL of 76%–100% [4, 28]. Maximum standardized uptake value (SUVmax) is higher in PCNSL than in gliomas [29, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…[ 18 F]-FDG PET has the ability to quantify regional differences in cerebral glucose metabolism, which can provide information about the distribution and activation of brain patterns. [ 18 F]-FDG PET has proven to be useful as a diagnostic tool in the clinical evaluation of CNS lesions in patients with HIV, particularly in those with CNS opportunistic infections where [ 18 F]-FDG PET can be used to distinguish between CNS malignancy and infection [31,32].…”
Section: Pet-fdg Brain Imaging In Handmentioning
confidence: 99%
“…Several studies have shown 18 F-FDG PET/CT scans to be particularly useful in differentiating infections such as toxoplasmosis from malignant lesions such as lymphoma or metastases in HIV-positive patients. In a study of 25 patients by Lewitschnig et al, 11 10 of 11 patients with a diagnosis of toxoplasmosis were correctly diagnosed by PET/CT scan showing 18 F-FDG uptake by the lesion to be less than that of normal brain cortex with a mean SUV max of 3.5 (range 1.9–5.8), while malignant lesions such as CNS lymphoma showed 18 F-FDG uptake greater than normal brain cortex with mean SUV max of 18.8 (range 12.4–29.9). Interestingly, two patients with tuberculosis also showed low 18 F-FDG uptake.…”
Section: Discussionmentioning
confidence: 97%